2020
DOI: 10.1093/infdis/jiaa478
|View full text |Cite
|
Sign up to set email alerts
|

Under the Radar: Epidemiology of Plasmodium ovale in the Democratic Republic of the Congo

Abstract: Background Plasmodium ovale is an understudied malaria species prevalent throughout much of sub-Saharan Africa. Little is known about the distribution of ovale malaria and risk factors associated with infection in areas of high malaria endemicity. Methods Using the nationally representative 2013 Democratic Republic of the Congo Demographic and Health Survey, we conducted a risk factor analysis for P. ovale infections in one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 36 publications
5
36
0
1
Order By: Relevance
“…Six years later, in 2013, the demographic and health survey revealed P. ovale spp. in 24/26 provinces of DRC, with an increased prevalence in several provinces [ 51 ]. This reflects a spread of P. ovale spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six years later, in 2013, the demographic and health survey revealed P. ovale spp. in 24/26 provinces of DRC, with an increased prevalence in several provinces [ 51 ]. This reflects a spread of P. ovale spp.…”
Section: Discussionmentioning
confidence: 99%
“…that urgently needs to be addressed, as DRC is the second most affected country by malaria in the world [ 1 ]. Several studies have also reported an equal distribution of P. ovale subspecies in AFR [ 21 , 32 , 35 , 51 ]. High prevalence of asymptomatic malaria including P. malariae [ 9 , 34 , 42 , 52 54 ] and P. ovale spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the limitations, we believe that this short report adds another piece to the puzzle of imported non-falciparum malaria. A recent study shows that P. ovale remains broadly prevalent in the DRC (prevalence estimate 0.8%; 95% confidence interval, 0.59–0.98%) [ 30 ]. We therefore want to raise clinicians’ awareness of the challenges posed by this neglected disease in both endemic and non-endemic settings.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are generally in-line with prior reports of non-falciparum infection among asymptomatic subjects in the DRC. [2325]…”
Section: Discussionmentioning
confidence: 99%